Design of a Drug-Delivery System Based On Polyacrylamide Hydrogels. Evaluation of Structural Properties - Ferreira, L. (2001)
It is well known that hydrogels can be suitable for biomedical, agricultural, and industrial applications. In particular, they have been widely used for the preparation of drug-delivery systems. The preparation and characterization of such a system should be useful for introducing students to these materials. This paper describes the preparation of polyacrylamide hydrogels having different crosslinking densities from the view of optimizing this system for acetylsalicylic acid (aspirin) release. The observations of equilibrium swelling, solute transport, and thermal analysis are related to the network structure of polyacrylamide hydrogel.